2013
DOI: 10.1074/jbc.m112.447524
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Repertoire of Amyloid Polymorphs by Co-polymerization of Related Protein Precursors

Abstract: Background: Amyloid fibrils in vivo are rarely composed of a single protein, yet the consequences of co-polymerization of different proteins are relatively poorly understood.Results: Fibrils formed by co-polymerizing two variants of β2-microglobulin were characterized alongside their homopolymer equivalents.Conclusion: The three fibril types have different structural and thermodynamic properties.Significance: Co-polymerization of protein precursors enhances the structural and thermodynamic diversity of amyloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 62 publications
7
67
0
1
Order By: Relevance
“…For example, WT β2m forms amyloids of different morphology and stability from solvent mixtures containing varying amounts of trifluoroethanol (37). Coprecipitation of WT β2m and the truncated ΔN6 variant was also shown to produce a distinct polymorph (38). Here, substitution of one or two hydrogens in Pro32 by fluorine elicits a similar effect.…”
Section: Discussionmentioning
confidence: 51%
“…For example, WT β2m forms amyloids of different morphology and stability from solvent mixtures containing varying amounts of trifluoroethanol (37). Coprecipitation of WT β2m and the truncated ΔN6 variant was also shown to produce a distinct polymorph (38). Here, substitution of one or two hydrogens in Pro32 by fluorine elicits a similar effect.…”
Section: Discussionmentioning
confidence: 51%
“…Perhaps unsurprisingly then, the heteropolymeric fibrils formed from β 2 m and ΔN6 do not resemble those formed from β 2 m alone at acidic pH or from ∆N6 alone at neutral pH. Instead biophysical experiments have shown that the heteropolymeric fibrils of β 2 m/ΔN6 form a unique polymorph that is thermodynamically less stable than both β 2 m and ∆N6 homopolymeric fibrils 30 . These findings show that the heteropolymorphic fibrils do not possess “average” structural or thermodynamic characteristics resulting from mixing of the two precursors.…”
Section: Condition 2: Co-aggregation Occurs By One Partner Protein Afmentioning
confidence: 97%
“…β 2 m forms amyloid fibrils in vivo resulting in the disease dialysis-related amyloidosis (DRA) 27 . However, in the absence of other co-factors or co-solvents human β 2 m will not form fibrils in vitro at neutral pH within an experimentally tractable timescale, 28 , 29 while ΔN6 is highly aggregation prone 20 , 30 . Surprisingly, when monomeric human β 2 m is mixed with monomeric ΔN6 fibril formation from both proteins occurs, resulting in heteropolymeric fibrils, even at neutral pH (Row 7 of Table 1).…”
Section: Condition 2: Co-aggregation Occurs By One Partner Protein Afmentioning
confidence: 99%
“…The fibril architecture can contain complicated structural features (Figure 1g-k), which likely form the basis of the pathological assembly and, therefore, are critical for understanding the folding and self-assembly pathway. In addition, amyloid fibrils can be polymorphic (17,45) and consist of mixtures of different proteins (46). Although amyloid fibrils are an important category of insoluble and noncrystalline proteins, their atomic-resolution structures are essentially inaccessible by solution NMR and X-ray diffraction; therefore, MAS NMR is the method of choice for characterizing these systems.…”
Section: Magic Angle Spinning Nmr Of Membrane Proteins and Amyloid Fimentioning
confidence: 99%